2011
DOI: 10.1021/nn2011865
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition-Grown Graphene: The Thinnest Solid Lubricant

Abstract: As an atomically thin material with low surface energy, graphene is an excellent candidate for reducing adhesion and friction when coated on various surfaces. Here, we demonstrate the superior adhesion and frictional characteristics of graphene films which were grown on Cu and Ni metal catalysts by chemical vapor deposition and transferred onto the SiO(2)/Si substrate. The graphene films effectively reduced the adhesion and friction forces, and multilayer graphene films that were a few nanometers thick had low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
274
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(296 citation statements)
references
References 31 publications
19
274
2
1
Order By: Relevance
“…This high amount of CNTs or whisker for toughening impedes considerably sintering of ceramics, which requires highpressure densification processes such as hot pressing and spark plasma sintering. Furthermore, in the case of CNT/ceramic composites [3][4][5][6][7][8] , in which the reinforcement concentration is high, the strength value was reported to be decreased as a result of relatively high structural flaw concentration 9 . The result that the peak K IC values were observed at the reinforcement concentration of 0.25-0.5 vol%, is consistent with theoretical graphene concentration (,0.34 vol%) for the complete monolayer coverage of alumina precursor (,300 nm) considering the theoretical surface area of single-layer graphene (,2630 m 2 /g).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This high amount of CNTs or whisker for toughening impedes considerably sintering of ceramics, which requires highpressure densification processes such as hot pressing and spark plasma sintering. Furthermore, in the case of CNT/ceramic composites [3][4][5][6][7][8] , in which the reinforcement concentration is high, the strength value was reported to be decreased as a result of relatively high structural flaw concentration 9 . The result that the peak K IC values were observed at the reinforcement concentration of 0.25-0.5 vol%, is consistent with theoretical graphene concentration (,0.34 vol%) for the complete monolayer coverage of alumina precursor (,300 nm) considering the theoretical surface area of single-layer graphene (,2630 m 2 /g).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of carbon nanotube (CNT), it has been reported that higher reinforcement concentration (1 , 10 vol%) was generally required for the toughening and strengthening of CNT/ceramic composites [2][3][4][5][6][7][8] . Moreover, graphene is a good candidate for solid lubrication that reduces the friction force between contact surfaces at micro-and nano-scale while protecting the coated surface [9][10] . A nanometer-thick surface layer of hard, strong, and lubricating graphene on ceramic grains can lead to a significant improvement in contact-damage resistance, such as wear resistance due to a tribological effect of 2-dimensional (2D) graphene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Template-assisted chemical vapour deposition growth: Chemical Vapour Deposition (CVD) is one of the ways to grow 3D grapheme [25][26][27][28][29][30][31][32]. It entails using pre-fabricated 3D metal substrates for example Ni foam.…”
Section: Direct Synthesis Of 3d Graphenementioning
confidence: 99%
“…Meanwhile, as the important method of graphene fabrication, the CVD has shown greater potential for fabricating large area single-crystal graphene. So many efforts have been dedicated to the researches on friction properties of CVD graphene [43][44][45]. Furthermore, the AFM has always been viewed as the invaluable tool for nanoscale character instead of atomic resolution.…”
Section: Introductionmentioning
confidence: 99%